Investigation of the impact of bacterial microencapsulation on natural product discovery - Tina Navaei; Elias Madadian; Bradley A. Haltli; Christopher Cartmell; Russell G. Kerr; Ali Ahmadi (Current Research in Biotechnology, 2023)
Developing new effective drugs to treat antibiotic resistant infections and cancer is urgently needed to reduce mortality due to these devastating diseases. Despite the promising potential of environmental microorganisms to produce such drugs, researchers are currently facing the problem of rediscovering known compounds. To address this challenge, the impact of microencapsulation on natural compound production was explored using, Kitasatospora cystarginea NRRL B-16505 which is known to produce cystargamide and the 20S proteasome inhibitory cystargolide. The current work postulates that the stress of microencapsulation process may induce secondary metabolism, potentially leading to the production of novel metabolites. Different microencapsulation techniques, including microfluidics, co-axial air flow printing, and emulsification, were compared in terms of bead size, cell viability, metabolite profile, and metabolite yields. This study has shown promising results that may be leading to the discovery of new bioactive compounds as well as activating the silent pathways for compound production. Nutrition deficiency, reduced Oxygen, presence of salt, heat shock, bead uniformity, and shear stress during microencapsulation are potential reasons for the production of these putatively novel chemicals.